Characterization, Concentration and Depositional History of Polycyclic Aromatic Hydrocarbons (Pahs) and Hopane from Selected Locations in Peninsular Malaysia - Sakari, Mahyar (2009)
Polycyclic aromatic hydrocarbons (PAHs) are one of the most important classes of pollutants in the marine environment that derive mostly from petroleum products. PAHs are ubiquitous compounds of concern due to its carcinogenic, mutagenic and toxic characteristics. Eight sedimentary cores were obtained from developed and developing areas around Peninsular Malaysia to investigate the historical profile of PAHs, their characteristics and its possible origins. Hopane composition and ratio were used as environmental forensic investigation biomarkers. The results showed that the PAHs varied from below detection limit amounts in offshore and less developed areas to near 4500 ngg-1 d. w. in developed and polluted locations. Most of the studied locations showed high contribution of PAHs from combusted fuel, coal, biomass and wood materials except for the southern part of Peninsular Malaysia which implied petroleum products release where shipping and marine transportation is active. The findings indicate pyrogenic and petrogenic PAHs comes from different intermediate materials such as asphalt, street dust, vehicular emission and crankcase oil with higher amounts near the city hinterland. Although there has been a decline of PAHs input into the marine environment in recent years, petroleum is shown to be a significant cause of marine pollution since the 1940’s. Climatic conditions play a role such as heavy daily rainfall, high organic content and suspended particle, accelerated wash off of contaminated materials into the marine environment via lateral transport. Results of statistical tests of PAHs specific compound suggest that PAHs in the deeper cores are derived naturally from biogeochemical processes.